A Fully Equational Proof of Parikh's Theorem - Aceto, Luca; Ésik, Zoltán; Ingólfsdóttir, Anna (BRICS Report Series, 2001)
We show that the validity of Parikh's theorem for context-free languages depends only on a few equational properties of least pre-fixed points. Moreover, we exhibit an infinite basis of mu-term equations of continuous commutative idempotent semirings.